Kinetic analysis of a unilateral snatch movement - Lake, J.; Lauder, M.; Dyson, R. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
The vertical ground reaction force (VGRF) of 7 weightlifters performing one-handed dumbbell power snatches with loads of 80%, 90% and 100% of 1RM were recorded at 500 Hz from 2 Kistler force platforms. There were no significant load or side effects for the pull phase peak VGRF or catch loading rates (P>0.05), although with the exception of the catch loading rate for the heaviest loads, non-lifting side values tended to be larger than those of the lifting side. In addition to this, lifting side pull phase duration was significantly longer than the non-lifting side (P<0.001). These results indicated that the dumbbell load distribution favoured one side affecting pull and catch symmetry and efficiency. This supports the suggestion that unilateral lifts may provide a different training stimulus that may be more specific for many sporting movements.